TRANSLATION IDEOLOGY ANALYSIS OF PROPER NOUNS IN THE NOVEL PRIDE AND PREJUDICE BY JANE AUSTEN - Ayu Bandu Retnomurti; Marmita Fiona (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: The research aims to describe translation ideology analysis of proper noun and todescribe the types of translation ideology which occur in the novel Pride and Prejudice. Themethod used in the research is a qualitative comparative approach by comparing the translation ofproper nouns in Source Language and Target Language. The results of the analysis show that thetranslator used foreignization ideology to transfer the meaning of the source text. The tendency isseen in the title of the text where the translator keeps the original title Pride and Prejudice insteadof transferring into Harga Diri dan Prasangka. The type of translation ideologies occur in thenovel are foreignization in which the translator stays faithful to the source language by preservingMr. Darcy into Mr. Darcy, and domestication in which the translator stays closer to the targetlanguage by transforming The Bennets into Keluarga Bennet.Key Words: Translation; Translation Ideology; Proper Noun; Novel